Numerical Investigation of Factors Influencing Multiple Hydraulic Fracture Propagation from Directional Long Boreholes in Coal Seam Roofs - Maolin Yang; Shuai Lv; Yu Meng; Xing Wang; Sicheng Wang; Jiangfu He (Applied Sciences)
The hanging of hard roofs in coal seams poses a significant threat to the safe mining of coal. Hydraulic fracturing is an important method to achieve the pre-weakening of coal seam roofs. Clarifying the scope of hydraulic fracturing in coal seam roofs and its influencing factors is a prerequisite for ensuring the effectiveness of the pre-weakening process. In this paper, we developed a fluid–structure coupling numerical simulation model for hydraulic fracturing based on the element damage theory, and have systematically examined the effects of both engineering parameters and geological factors on the hydraulic fracture propagation behavior of the segmented fracturing of coal seam roofs. Results indicate that increasing the injection rate can significantly enhance fracture propagation length. A larger stress difference directs fractures along the maximum principal stress direction and effectively extends their length. Additionally, increasing the spacing between fracture stages reduces stress interference between clusters, leading to a transition from asymmetric to uniform fracture propagation. To validate the numerical simulation results, we conducted a field test on the hydraulic fracturing of the coal seam roof, and monitored the affected area by using transient electromagnetic and microseismic monitoring techniques. Monitoring results indicated that the effective impact range of field hydraulic fracturing was consistent with the numerical simulation results. Through the systematic monitoring of support resistance and coal body stress, the supporting resistance in the fractured zone decreased by 25.10%, and the coal seam stress in the fractured zone exhibited a 1 MPa reduction. Observations demonstrate the significant effectiveness of hydraulic fracturing in regional control of the coal seam roof. This study combines numerical simulation with engineering practice to investigate hydraulic fracturing performance under varying operational conditions, with the findings providing robust technical support for safe and efficient mining production.